Analysis of Students’ Critical Thinking Skills by Applying Flipped Classroom Learning Model using Powtoon Application on The Topic of Salt Hydrolysis - Paristiowati, Maria; Nanda, Elsa Vera; Putri Hasibuan, Nur Azizah; Ilmana, Miska Zidna (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2022)
This study aims to determine students' critical thinking skills by applying flipped classrooms using the Powtoon application on the topic of salt hydrolysis. This study, which included 36 participants—15 men and 21 women—used a descriptive methodology and was carried out at one of Jakarta's public high schools. The instrument used was an observation sheet to observe the flipped classroom model’s learning process, critical thinking skills tests, reflective journals, and depth interviews. The flipped classroom method entails four steps: pre-class by studying independently and providing stimuli. In-class by fostering critical thinking; and post-class by evaluating. Combining asynchronous and synchronous activities was the process. Students learn independently during the pre-class stage by answering pre-learning questions and watching videos. During the class phase, Zoom meetings are used for synchronous learning to discuss salt hydrolysis applications in particular contexts. Discussion assignments on the salt hydrolysis case help students learn asynchronously after class. The study results showed that the flipped classroom using the Powtoon application can be an alternative for distance learning and can influence the students’ critical thinking at a very good level. It also helps them be more active and critical in learning, like exchanging opinions with others and doing assignments on the topic of salt hydrolysis.